PENERAPAN FORMULA BENEISH M-SCORE DAN ANALISIS DISKRIMINAN LINIER UNTUK KLASIFIKASI PERUSAHAAN MANIPULATOR DAN NON-MANIPULATOR (Studi Kasus Di Bursa Efek Indonesia Tahun 2013) - Issabella Marsasella Christy; Sugito Sugito; Abdul Hoyyi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Discriminant analysis is a statistical analysis method is used to classify an individual into a certain group which has determined based on the independent variables. In linear discriminant analysis, there are two assumptions to be fulfilled i.e. independent variables have to be multivariate normal distributed and variance covariance matrix of the observed two groups are the same. In this graduating paper is applied Beneish M-Score formula and linier discriminant analysis for classification of cases companies manipulators and non-manipulators are listed in Indonesia Stock Exchange in 2013. Linear discriminant function to continue Beneish M-Score formula to predict the classification, in order to obtain the percentage of fault classification, to determine the size of the performance of linear discriminant function. Percentage of classification error of 2,70 percent. Keywords: Beneish M-Score, Linear Discriminant Analysis